Penyuluhan Kesehatan Perilaku Hidup Bersih dan Sehat Melalui Kegiatan Mencuci Tangan Pakai Sabun dengan Media Permainan Tradisional Engklek pada Anak TK ABA Ciamis - Fitriani Fajriah; Amalia Pasca Fitri; Dian Andriani; Noneng Nuraida; Riska Fadilah; Vina Nurkania (Yayasan Inspirasi El Burhani, 2021)
Introduction: The spread of disease is generally caused by a lack of knowledge about clean and healthy living behavior (PHBS). Clean and healthy living behavior is a health behavior that can be done consciously so that family members can help themselves in the health sector and can play an active role in health activities in the community. Washing hands with soap is one of the efforts to prevent and protect the body against infectious diseases. The traditional engklek game is one of the games played and favored by children. Objective: Applied in daily activities both within the family and at school to form clean and healthy living behavior in children. Method: The promotion of health research was used in the methods of phbs education and demonstration of Wash your hands using soap and running water and engklek games. This Health Promotion was carried out with 6 students located in ABA Kindergarten, Ciamis District, Ciamis Regency with a total of 43 children as respondents and accompanied by the kindergarten teacher. Health Promotion This is carried out through 4 stages, namely 1) selection of targets and places, 2) preparation of suggestions and infrastructure, 3) implementation of activities, 4) evaluation. Result: implemented of health promotion for children in ABA Ciamis Kindergarten regarding Clean and Healthy Living Behavior about Washing hands with soap and running water produced significant results because previously the children in ABA Ciamis Kindergarten had implemented it so that it became a tradition that was often done and became a habit everyday Conclussion: Through the implementation of the activity